Dual functionalized imidazolium ionic liquids as a green solvent for extractive desulfurization of fuel oil: Toxicology and mechanistic studies - Raj, J.J. (2019)
Readily biodegradable and âpractically non-toxicâ dual functionalized imidazolium ionic liquids (ILs) carrying nitrile and varying number of ether group were developed to improve the extractive desulfurization performance and ecotoxicity of ILs. Dicyanamide (N(CN) 2 ), trifluoroacetate (CF 3 COO) and bis(trifluoromethylsulfonyl)imide (NTf 2 ) were selected as anions. Evaluation of thermophysical properties of the synthesized ILs revealed that bis(trifluoromethylsulfonyl)imide anion based ILs have lowest viscosity, which contributed to excellent mass transfer and enhanced desulfurization performance. The effect of temperature, time and mass ratio (ILs: model oil) were investigated for extractive desulfurization and the performance of ILs were in the anion order; dicyanamide < trifluoroacetate < bis(trifluoromethylsulfonyl)imide. Dibenzothiophene was more selectively extracted over 4,6- dimethyldibenzothiophene. Increasing alkoxy group on the cation side chain improved the desulfurization efficiency. More than 70 of dibenzothiophene was extracted in 15 min (single stage extraction) with a mass ratio of 1.5:1 at 25 Â°C by bis(trifluoromethylsulfonyl)imide anion based ILs with three ether groups on the imidazolium cation. Conductor like Screening Model for Real Solvents tool (COSMO-RS) and FTIR spectroscopy study revealed that interaction between dibenzothiophene and ILs were mainly dominated by Ï-Ï interaction and hydrogen bonding. The microbial toxicity and biodegradability assessment indicated that ILs were âpractically harmlessâ and âreadily biodegradableâ through the incorporation of alkoxy groups on the cationic core of bis(trifluoromethylsulfonyl)imide anion based ILs. The ILs can be reused more than 8 cycles for the desulfurization process without regeneration. Â© 2018